Hubungan Keterlibatan dalam Permainan Tradisional dengan Sikap Tanggung Jawab Mahasiswa PGSD - Rahmat Darmawan (GENIUS: Jurnal Inovasi Pendidikan dan Pembelajaran, 2025)
This study was motivated by the importance of traditional games as a medium for character education among prospective elementary school teachers. Traditional games not only provide recreational experiences but also foster responsibility, cooperation, and adherence to rules. This research aimed to examine the relationship between students’ involvement in traditional games and their sense of responsibility. The study employed a quantitative approach with a descriptive correlational design. The participants were 20 first-semester students of the Primary School Teacher Education Study Program who had participated in traditional games such as Bentengan, Kasti, and Boy-boyan. Data were collected using a four-point Likert scale questionnaire and analyzed using the Pearson Product Moment correlation test. The results showed a correlation coefficient of r = 0.961 with p < 0.001, indicating a very strong and significant positive relationship between students’ involvement in traditional games and their responsibility. These findings suggest that the higher the students’ involvement in traditional games, the greater their sense of responsibility. Thus, traditional games are effective as a medium for character education in teacher education programs